ANALISIS PEMANFAATAN APLIKASI GEMINI DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS XI SMA - Windy E. M. Ohoiner; Fatimah Sialana; Aisa Abas (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
This study aims to analyze the use of the Gemini application in increasing student interest in learning Pancasila education in grade XI at SMA Negeri 1 Tual. Advances in information technology have changed students' learning patterns. Today's young generation, especially Generation Z, tends to be more interested in interactive, visual, and digital technology-based learning media. This phenomenon requires teachers to innovate in utilizing technology as a learning tool. The younger generation today, especially Generation Z, tends to be more interested in interactive, visual, and technology-based learning media. This phenomenon requires teachers to innovate in utilizing technology as a learning tool, including in teaching Pancasila education material, which has often been considered monotonous by some students. This study uses a qualitative approach with a descriptive research type. The subjects of this research consisted of students and teachers. The data collection techniques were observation and documentation. The data were analyzed using qualitative descriptive analysis. The results of the study showed that the use of the Gemini application in Pancasila Education learning in class XI at SMA Negeri 1 Tual has been running well as a learning support medium. This application helps students understand conceptual and normative material through the presentation of information that is simpler, contextual, and easy to understand, as well as supporting the role of teachers in planning and implementing learning. The Gemini application plays a role in shaping the character of students' digital citizenship, particularly in fostering critical thinking, responsibility, and ethics in the use of digital technology. Students not only use Gemini to obtain information, but also learn to select, evaluate, and use information wisely in accordance with the values of Pancasila. The use of the Gemini application in building students' interest in learning is influenced by supporting and inhibiting factors. Supporting factors include school support, teacher readiness, ease of use, and the characteristics of students as the digital generation. Meanwhile, inhibiting factors include limited internet access, differences in digital literacy, and the potential for distraction from the use of gadgets in learning. ABSTRAK Penelitian ini bertujuan untuk menganalisis  analisis pemanfaatan aplikasi gemini dalam meningkatkan minat belajar siswa pada pembelajaran pendidikan pancasila di kelas xi SMA Negeri 1 Tual. Kemajuan teknologi informasi telah mengubah pola belajar siswa. Generasi muda saat ini, khususnya generasi Z, cenderung lebih tertarik pada media pembelajaran yang interaktif, visual, dan berbasis teknologi digital Fenomena ini menuntut guru untuk berinovasi dalam memanfaatkan teknologi sebagai sarana pembelajaran, termasuk dalam mengajarkan materi Pendidikan Pancasila yang selama ini sering dianggap monoton oleh sebagian siswa. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Subjek penelitian ini terdiri dari siswa dan guru. Teknik pengumpulan  data adalah observasi dan dokumentasi. data dianalisis secara deskriptif kualitatif. Hasil penelitian bahwa Pemanfaatan aplikasi Gemini dalam pembelajaran Pendidikan Pancasila di kelas. XI SMA Negeri 1 Tual telah berjalan dengan baik sebagai media pendukung pembelajaran. Aplikasi ini membantu siswa memahami materi yang bersifat konseptual dan normatif melalui penyajian informasi yang lebih sederhana, kontekstual, dan mudah dipahami, serta mendukung peran guru dalam perencanaan dan pelaksanaan pembelajaran. Aplikasi Gemini berperan dalam membentuk karakter kewarganegaraan digital siswa, khususnya dalam menumbuhkan sikap kritis, tanggung jawab, dan etika dalam menggunakan teknologi digital. Siswa tidak hanya memanfaatkan Gemini untuk memperoleh informasi, tetapi juga belajar menyeleksi, mengevaluasi, dan menggunakan informasi secara bijak sesuai dengan nilai-nilai Pancasila.Pemanfaatan aplikasi Gemini dalam membangun minat belajar siswa dipengaruhi oleh faktor pendukung dan penghambat. Faktor pendukung meliputi dukungan sekolah, kesiapan guru, kemudahan aplikasi, dan karakteristik siswa sebagai generasi digital. Sementara itu, faktor penghambat mencakup keterbatasan jaringan internet, perbedaan literasi digital, serta potensi distraksi penggunaan gawai dalam pembelajaran.